Exploring the Impact of Corporate Risk, Sales Growth, Liquidity, and Profitability on Tax Evasion Strategies - Cindy Amelia Nurmanita; Suhirman Madjid (Santoso Academy Network, 2026)
The purpose of this study is to examine how tax avoidance is impacted by sales growth, firm risk, profitability, and liquidity. A sample of ten businesses was chosen via purposive sampling, and the population is made up of manufacturing businesses in the health and pharmaceutical subsectors. Secondary data from business financial accounts is used in this quantitative analysis. Multiple linear regression was used to analyze the data, along with descriptive statistics, traditional assumption testing, and hypothesis testing. The findings show that while firm risk and current ratio have no discernible effect on tax evasion, sales growth and return on assets (profitability) do. The results imply that businesses need to closely monitor financial metrics in order to achieve equilibrium between tax efficiency and compliance. Managers should enhance profitability through operational efficiency, manage risks effectively, and maintain liquidity to minimize the incentive for tax avoidance. This study adds to the body of literature by providing empirical data from a little-studied Indonesian industry, educating policymakers, tax authorities, and business managers about the financial aspects that affect tax behavior, assisting in the creation of efficient tax laws, and corporate governance strategies.